2011
DOI: 10.1093/europace/eur099
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial pacing improves atrial haemodynamics and atrioventricular timing compared with pacing from the right atrial appendage

Abstract: Multisite atrial pacing results in favourable acute atrial haemodynamics and left AV synchrony. This may be a solution in pacemaker patients with interatrial conduction delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…In a study by Burri et al, 24 patients undergoing radiofrequency ablation for paroxysmal AF were evaluated with pacing at multiple different sites. These included the high IAS, the distal and proximal coronary sinus (CSD and CSP, respectively), as well as simultaneous IAS/CSD biatrial pacing (BiA) [42]. Hemodynamic properties of the left atria were measured during these pacing modes and compared with those while pacing from the right atrial appendage (RAA).…”
Section: Biatrial Pacing In Iabmentioning
confidence: 99%
“…In a study by Burri et al, 24 patients undergoing radiofrequency ablation for paroxysmal AF were evaluated with pacing at multiple different sites. These included the high IAS, the distal and proximal coronary sinus (CSD and CSP, respectively), as well as simultaneous IAS/CSD biatrial pacing (BiA) [42]. Hemodynamic properties of the left atria were measured during these pacing modes and compared with those while pacing from the right atrial appendage (RAA).…”
Section: Biatrial Pacing In Iabmentioning
confidence: 99%
“…Furthermore, populations in both studies were small and consisted of only 8 and 14 patients, respectively. Furthermore, patients with prolonged A-V conduction and heart failure associated with interventricular conduction abnormalities were not excluded, which might have blunted the effect of BiA and RAA pacing on cardiac hemodynamics [16]. The population in the study of Levy et al [13] consisted of patients with bradycardia–tachycardia syndrome, and the interatrial conduction was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…The population in the study of Levy et al [13] consisted of patients with bradycardia–tachycardia syndrome, and the interatrial conduction was not specified. It has been already demonstrated that patients without baseline IAB do not benefit from BiA pacing compared to sinus rhythm, while RAA pacing has an unfavorable hemodynamic effect in this group [16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an early report in brady-tachy population without clear identification of HFpEF, dual site atrial pacing combined with antiarrhythmic drugs and/or limited ablation showed favorable left atrial and ventricular hemodynamic effects as well as rhythm control efficacy [15,16]. Early acute studies with biatrial dual site pacing have shown acute hemodynamic benefits for left atrial and cardiac performance [17,18]. However, the electrophysiologic community focused largely on the beneficial effects of electrical atrial resynchronization and had limited attention span for its hemodynamic benefits.…”
mentioning
confidence: 99%